THE INFLUENCE OF WORKLOAD, WORK FATIGUE, SELF-EFFICACY AND WORK ENVIRONMENT ON THE PERFORMANCE OF MEDICAL WORKERS POST THE REVOCATION OF PPKM AT XYZ HOSPITAL IN GIANYAR - Putu Chintya Nitiyani Santika; Rudy Pramono (SEAN Institute, 2023)
This study was to analyze the effect of workload, work fatigue, self-efficacy, and work environment on the performance of medical personnel after the revocation of PPKM at XYZ Hospital. In this study, the cross-sectional method was used to obtain quantitative data from online questionnaires. The questionnaire was modified based on pre-existing questions from previous literature. Data was collected purposively from a group of 142 medical personnel including doctors, dentists, nurses and midwives who had worked in XYZ private hospitals for at least one year using a non-probability sampling technique. PLS-SEM software is then used to analyze it. The results showed that workload had a positive and significant effect on the performance of medical staff at XYZ General Hospital, Gianyar, Bali, work fatigue had a positive but not significant effect on the performance of XYZ General Hospital medical staff, Gianyar, Bali, self-efficacy had a positive and negative effect. supported on the performance of medical staff at XYZ General Hospital, Gianyar, Bali, the work environment has a positive influence and is supported on the performance of XYZ General Hospital medical staff, Gianyar, Bali. The implications of this research for the performance of medical staff at XYZ General Hospital, Gianyar, Bali are that it requires periodic evaluation of factors affecting workload, workload, work fatigue, self-efficacy, and work environment after the revocation of PPKM.